Educational Model of Economic Cycles - Liapzev, Alexander (Computer Tools in Education, 2022)
A training model describing economic cycles, based on the well-known Goodwin model is proposed. The modification of the model is described, that allow to use it to carry out numerical experiment in teaching course of modeling with the help of computer. It is shown that the numerical results obtained using the proposed model correspond well to the analytical analysis of the properties of the Goodwin model, which is usually given in the literature.